Marine teleost ortholog of catalase from rock bream (Oplegnathus fasciatus): Moleculr perspectives from genomic organization to enzymatic behavior with respect to its potent antioxidant properties - Elvitigala, D. A. S.; Premachandra, H. K. A.; Whang, I.; Priyathilaka, T. T.; Kim, E.; Lim, B. S.; Jung, H.B.; Yeo, S. Y.; Park, H. C.; Lee, J. (Elsevier, 2013)
Catalases are well known antioxidant enzymes that can mainly dismutate hydrogen peroxide into water and oxygen in order to prevent oxidative stress. The complete genomic DNA (gDNA) sequence of the catalase gene from rock bream (Oplegnathus fasciatus) was identified from our custom-constructed BAC genomic DNA library and designated as RbCat. RbCat consists of 13 exons, separated by 12 introns, within a 13,722-bp gDNA sequence. The complete cDNA sequence (3303 bp) of RbCat is comprised of a 1581-bp coding region, encoding a peptide of 527 amino acids (aa) in length, with a predicted molecular mass of 60 kDa and a theoretical isoelectric point of 8.34. The anticipated promoter region of RbCat contains several transcription factor-binding sites, including sites that bind with immune- and antioxidantresponsive signaling molecules, suggesting its substantial transcriptional regulation. RbCat resembles the typical catalase family signature, i.e., it is composed of the catalase proximal active site motif along with a catalase proximal heme-ligand signature motif and shares great homology with its fish counterparts. According to multiple sequence alignment, functionally important amino acids present in RbCat were thoroughly conserved among its vertebrate counterparts. Phylogenetic analysis revealed that RbCat evolved from a vertebrate origin, and further positioned it in the fish clade. Recombinant RbCat had noticeable peroxidase activity against its substrate, hydrogen peroxide, in a dose-dependent manner. However, it demonstrated substantial peroxidase activity within a broad range of temperatures and pH values. Constitutive RbCat mRNA expression of different magnitudes was detected in a tissue-specific manner, suggesting its diverse role in physiology with respect to the tissue type. Moreover, immune challenge experiments using Edwardsiella tarda and rock bream iridovirus (RBIV) as live pathogens and polyinosinic:polycytidylic acid and lipopolysaccharide as mitogens revealed that the transcription of RbCat can be modulated by immune stimulation. Collectively, the results obtained in this study suggest that RbCat can function as a potent antioxidant enzyme in rock bream and may play a role in postimmune responses with respect to its peroxidase activity.
Keywords: Catalase; Rock bream; Genomic organization; Transcriptional profiling; Peroxidase activity